2020
DOI: 10.1371/journal.pone.0234584
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Japanese encephalitis virus as a cause of acute encephalitis in southern Pakistan, April 2015–January 2018

Abstract: Background Japanese encephalitis (JE) occurs in fewer than 1% of JE virus (JEV) infections, often with catastrophic sequelae including death and neuropsychiatric disability. JEV transmission in Pakistan was documented in 1980s and 1990s, but recent evidence is lacking. Our objective was to investigate JEV as a cause of acute encephalitis in Pakistan. Methods Persons aged �1 month with possible JE admitted to two acute care hospitals in Karachi, Pakistan from April 2015 to January 2018 were enrolled. Cerebrospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The presence of the mosquito vector, amplifying hosts, and rice irrigation in Pakistan continue to pose a risk for the transmission of JEV. 2 Although there is no ongoing active surveillance program for JEV in the country, evidence of JEV presence has been reported in Pakistan particularly in Sindh. [2][3][4] A recent sero-survey in Karachi, investigating patients with acute undifferentiated febrile illness, provided additional confirmation of the presence of JEV in the country when antibodies against the virus were detected in 50 out of 115 samples.…”
Section: Dear Editormentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of the mosquito vector, amplifying hosts, and rice irrigation in Pakistan continue to pose a risk for the transmission of JEV. 2 Although there is no ongoing active surveillance program for JEV in the country, evidence of JEV presence has been reported in Pakistan particularly in Sindh. [2][3][4] A recent sero-survey in Karachi, investigating patients with acute undifferentiated febrile illness, provided additional confirmation of the presence of JEV in the country when antibodies against the virus were detected in 50 out of 115 samples.…”
Section: Dear Editormentioning
confidence: 99%
“…2 Although there is no ongoing active surveillance program for JEV in the country, evidence of JEV presence has been reported in Pakistan particularly in Sindh. [2][3][4] A recent sero-survey in Karachi, investigating patients with acute undifferentiated febrile illness, provided additional confirmation of the presence of JEV in the country when antibodies against the virus were detected in 50 out of 115 samples. 4 Additionally, among 360 healthy blood donors screened by Khan et al, one sample was found to have antibodies against JEV, with an overall donor seropositivity for arboviruses being 7.2%.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…South Asia, Central Asia, and Southeast Asia were the top three GBD regions with the highest ASMRs in 2019 (more than 1. 25), where all the ASMRs of encephalitis declined significantly over the past 30 years (Table S2). The lowest ASMR was found in Australasia (0.06), followed by Oceania, and Southern Sub-Saharan Africa.…”
Section: Variation In Encephalitis Burden At Regional and National Levelmentioning
confidence: 99%